Mechanical and morphological determinants of peak power output in elite cyclists - Kordi, M.; Folland, J.; Goodall, S.; Haralabidis, N.; Maden-Wilkinson, T.; Sarika Patel, T.; Leeder, J.; Barratt, P.; Howatson, G. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Mechanical peak power output (PPO) is a determinant of performance in sprint cycling. The purpose of this study was to examine the relationship between PPO and putative physiological determinants of PPO in elite cyclists, and to compare sprint performance between elite sprint and endurance cyclists. Thirty-five elite cyclists (18 endurance; 17 sprint) performed duplicate sprint cycling laboratory tests to establish PPO and its mechanical components. Quadriceps femoris (QVOL) and hamstring muscle volume (HAMVOL) were assessed with MRI, vastus lateralis pennation angle (P?VL) and fascicle length (FLVL) were determined with ultrasound imaging, and neuromuscular activation of three muscles was assessed using EMG at PPO during sprint cycling. For the whole cohort, there was a wide variability in PPO (range 775-2025 W) with very large, positive, bivariate relationships between PPO and QVOL (r = .87), HAMVOL (r = .71), and P?VL (r = .81). Step-wise multiple regression analysis revealed that 87% of the variability in PPO between cyclists was explained by two variables QVOL (76%) and P?VL (11%). The sprint cyclists had greater PPO (+61%; P < .001 vs endurance), larger QVOL (P < .001), and BFVOL (P < .001) as well as more pennate vastus lateralis muscles (P < .001). These findings emphasize the importance of quadriceps muscle morphology for sprint cycling events.